1997
DOI: 10.1002/(sici)1097-4687(199712)234:3<223::aid-jmor2>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of spermatogenesis and the spermatozoon in Postorchigenes gymnesicus (Trematoda, Lecithodendriidae)

Abstract: An ultrastructural study of spermatogenesis, spermiogenesis, and spermatozoa in Postorchigenes gymnesicus is presented. Cytoplasmic projections originating in nurse cells surround the spermatogonia, which are located at the periphery of the testes. Primary spermatocytes attached to a cytophore show synaptonemal complexes and a pair of centrioles. Spermiogenesis begins with the appearance of a cytoskeletal structure formed by an intercentriolar body and two perpendicular centrioles. An axoneme and a striated ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
46
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 0 publications
9
46
1
Order By: Relevance
“…The ultrastructural organization of the tests and cytological transformations during the spermatogenesis and spermiogenesis in S. godoyi are in agreement with those reported for other Digenea, including Haematoloechus medioplexus (by Burton 1972), Cryptocotyle lingua (by Rees 1979), Corrigia vitta (by Robinson & Halton 1982), Bucephaloides gracilescens (by Erwin & Halton 1983), Postorchigenes gymnesicus (by Gracenea et al 1997), Mesocoelium monas (by . The exceptions of this general pattern are Schistosoma mansoni that has one flagellum with a 9+1 and 9+0 configurations (Kitajima et al 1976, Justine & Mattei 1981 and Didymozoon sp.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The ultrastructural organization of the tests and cytological transformations during the spermatogenesis and spermiogenesis in S. godoyi are in agreement with those reported for other Digenea, including Haematoloechus medioplexus (by Burton 1972), Cryptocotyle lingua (by Rees 1979), Corrigia vitta (by Robinson & Halton 1982), Bucephaloides gracilescens (by Erwin & Halton 1983), Postorchigenes gymnesicus (by Gracenea et al 1997), Mesocoelium monas (by . The exceptions of this general pattern are Schistosoma mansoni that has one flagellum with a 9+1 and 9+0 configurations (Kitajima et al 1976, Justine & Mattei 1981 and Didymozoon sp.…”
Section: Discussionsupporting
confidence: 87%
“…Most studies on sperm ultrastructure have been described in Monogenea (Justine 1992, 1993, Rohde & Watson 1994a,b, Baptista-Farias et al 1995, 1999, Hathaway et al 1995, Harris et al 1997. Spermiogenesis presents minor differences in Digenea, suggesting different evolutionary levels within the groups (Hendow & James 1988, Cifrian et al 1993, Gracenea et al 1997). The present study describes the ultrastructure of spermatogenesis and the fine structure of the mature spermatozoon in a digenean species, Saccocoelioides godoyi, parasite of the freshwater fish, Leporinus friderici.…”
mentioning
confidence: 99%
“…Moreover, in several sections during the final stages of spermiogenesis, the mitochondrion is observed in migration. Contrarily, a mitochondrial migration before nuclear migration has been reported in the spermiogenesis of Dicrocoelium dendriticum (Cifrian et al 1993), Postorchigenes gymnesicus (Gracenea et al 1997) and R. exasperatum (Bakhoum et al 2011b).…”
Section: Spermiogenesismentioning
confidence: 83%
“…Such an anterior tip exhibiting both axonemes is rare in digenean spermatozoa. In fact, most species described until now present only one axoneme as in P. gymnesicus, Anisocoelium capitellatum or D. subclavatus (Gracenea et al 1997, Ternengo et al 2009, Bakhoum et al 2011a.…”
Section: Spermatozoonmentioning
confidence: 99%
“…However, striated rootlets are apparent in spermatozoa from another inseminating characid, Macropsobrycon uruguayanae (Burns et al, 1998), and in all families of elopomorph fishes except Muraenidae (Jamieson, 1991). Striated rootlets are also present in the spermatozoa of many invertebrates (e.g., Platyhelminthes; Justine, 1995), as well as in the spermatids of Postorchigenes (Platyhelminthes: Trematoda: Lecithodendriidae; Gracenea et al, 1997). Work by Yang et al (2002Yang et al ( , 2005 on striated rootlets of ciliated cells demonstrated that rootlets are critical structures for support of cilia and are composed of a large protein called rootletin.…”
Section: Discussionmentioning
confidence: 99%